Epidemiology And Morphology Of Lungworm (Dictyocaulus Viviparus), And Its Associated Lung Pathology In Cattle And Buffaloes In Peninsular Malaysia - Htun, Lat Lat (2007)

(untitled)
Bovine dictyocaulosis is an important parasitic disease of cattle and buffaloes and is caused by the lungworm, Dictyocaulus viviparus. The parasite is an important cause of lung infection especially in the temperate regions of the world. While the documentation on bovine lungworm is vast in the temperate, it is very sporadic and limited in the tropics. In Malaysia, a tropical country, the occurrence of lungworm infections in cattle and buffaloes has been anecdotal. The present study was carried out to detect the presence of lungworm infections in cattle and buffaloes, to determine the prevalence of lungworm infection in cattle and buffaloes, to identify the risk factors associated with bovine lungworm infection, to compare the morphology of egg, first stage larvae (L1) and adult stage of Malaysian bovine lungworm with those of D. viviparus from published reports and Sweden and to compare the histopathological lesions of lungs infected with Malaysian bovine lungworm and those of lungs infected with D. viviparus.A retrospective examination of available records and data was carried out to investigate the presence of lungworm infections in Peninsular Malaysia. Two studies were carried out to address the objective. In the first study, an investigation on lungworm disease outbreak in a beef breeding farm was conducted. It was found that the yearly lungworm-infection mortality rate within the seven-year period was 0.31%. Among the cases, more than half (67%) were male and 33% were females. Seventy-five percent of lungworm infection deaths occurred in calves between the ages of six and 12 months, and 25% occurred in cattle aged 12 to 19 months. Most of the deaths occurred in November (19%) and May (17%). In the second study, data of condemnation of lungs and reasons of condemnation between 1998 and 2004 was collected at the Department of Veterinary Services Headquarters in Kuala Lumpur. Parasitic lung condemnation from all slaughtered animals was 0.11%. The prevalence of parasitic infection in the lungs was found much higher in buffaloes than in cattle (t = -3.906, p = 0.002). A cross-sectional study was carried out in four large scale farms (Farms A, B, C and D) and three dairy smallholdings (Farm E) to detect and determine the prevalence of lungworm infection and to identify the risk factors. Blood and faecal sampling on each farm, except Farm E, was performed every two months for a period of seven months. Farm E was sampled only once. Questionnaires on individual animals, farm management and disease occurrence were developed and the data were collected at the time of blood and faecal sampling. Meteorological data was collected from the Climate Division, Malaysian Meteorological Service. The total blood and faecal samples collected from the farms were 602. Baermannisation was performed for parasitological diagnosis and enzyme-link-immunosorbent assay was conducted for serodiagnosis. The prevalence of lungworm infection based on baermannisation was 4.7%. The highest prevalence was found in Farm E. Using binary logistic regression analysis, gender and the interaction between monthly temperature and monthly rainfall were identified as the statistically significant risk factors for bovine lungworm infection. The likelihood of lungworm infection was about four times greater when the monthly rainfall was >100 mm and the monthly temperature was >27°C to 29.1°C than when the monthly rainfall was <100 mm and when the temperature was <27°C (p = 0.002). Female animals were about 2.9 times less likely to be infected than male animals (p = 0.01). Another cross-sectional study was carried out where 11 out of 25 abattoirs in Peninsular Malaysia were visited and slaughtered animals were examined. Animals slaughtered at Universiti Putra Malaysia (UPM) mosque during festivals were also examined. Among the total of 283 lungs from 260 cattle and 23 buffaloes sampled, lungworm was found in three Kedah-Kelantan (KK) cattle (1.1%). The morphological evaluation of egg, L1 and adult worm of the Malaysian bovine lungworm were conducted by comparing with those of D. viviparus from published reports and Sweden. Histopathological lesions of infected lungs were also examined. Based on the morphology of the lungworm and the histopathological changes of the affected lungs, the Malaysian bovine lungworm is believed to be most likely D. viviparus.In conclusion, bovine lungworm infection in the Malaysian cattle and buffaloes can be detected and the prevalence is low. The disease occurrence was associated with the gender of the animals, and the climatic conditions. Based on the morphology of vi the lungworm and the histopathological changes of the affected lungs, the Malaysian bovine lungworm is believed to be D. viviparus.